2004
DOI: 10.1111/j.1530-0277.2004.tb03229.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prostaglandin E Receptor Subtype EP4 Selective Agonist on the Secretion of Tumor Necrosis Factor‐α by Macrophages in Acute Ethanol‐Loaded Rats

Abstract: Background: It is suggested that endotoxin and proinflammatory cytokines play an important role in the development and progression of alcoholic liver disease. Recently, a prostaglandin receptor subtype EP4 agonist with cytoprotective effect has been developed. We examined the efficacy of an EP4 agonist ONO-AE1-437 on tumor necrosis factor-␣ (TNF-␣) secretion of Kupffer cells, splenic macrophages, and alveolar macrophages in acute ethanol-loaded rats.Methods: Kupffer cells, splenic macrophages, and alveolar mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…We believe that stimulation of the EP4 receptor by PGE 2 in vivo can activate a phosphoinositide 3‐kinase (PI3‐K)/ERK signaling pathway that might control pro‐inflammatory cytokines and chemokines. In ischemic brain, this pathway might aggravate the outcome of acute ischemic stroke (Nawashiro et al ., 1997; Nakatani et al ., 2004). It also has been proposed, in a neuronal toxicity paradigm, that activation of EP4 receptors stimulates protein kinase A, PI3‐K and protein kinase C, and that cooperation between these multiple intracellular pathways might lead to the Tcf/Lef‐1‐dependent transcriptional activation of growth‐related genes that is required to stimulate neuronal survival (Lee et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…We believe that stimulation of the EP4 receptor by PGE 2 in vivo can activate a phosphoinositide 3‐kinase (PI3‐K)/ERK signaling pathway that might control pro‐inflammatory cytokines and chemokines. In ischemic brain, this pathway might aggravate the outcome of acute ischemic stroke (Nawashiro et al ., 1997; Nakatani et al ., 2004). It also has been proposed, in a neuronal toxicity paradigm, that activation of EP4 receptors stimulates protein kinase A, PI3‐K and protein kinase C, and that cooperation between these multiple intracellular pathways might lead to the Tcf/Lef‐1‐dependent transcriptional activation of growth‐related genes that is required to stimulate neuronal survival (Lee et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Through experiments with the genetic deletion of EP4 in macrophages, Nataraj et al (2001) demonstrated that suppression of TNF-a production was mediated by EP4. In vitro pharmacological studies also demonstrated that EP4 inhibited TNF-a production in monocytes/macrophages in humans (Meja et al, 1997;Ratcliffe et al, 2007), mice (Katsuyama et al, 1998a;Yamane et al, 2000;Ikegami et al, 2001;Akaogi et al, 2004;Nakatani et al, 2004), and rats (Treffkorn et al, 2004;Aronoff et al, 2008).…”
Section: B Cancermentioning
confidence: 92%
“…EP2 and EP4 receptors seem to signal by increasing cAMP while EP3 receptors act via reduced cAMP levels and EP1 receptors via increased Ca (Breyer et al, 2001). Experiments with EP4 receptor agonists ONO-4819 and ONO-AE1-437 suggest that the EP4 receptor is involved in protection against liver injury induced by LPS or D-galactosamine (Kasai et al, 2001) and also in the response of macrophages isolated after acute ethanol exposure (Nakatani et al, 2004).…”
Section: Control Ethanolmentioning
confidence: 99%
“…There is also evidence that Kupffer cells activated by ethanol produce PGE 2, which can stimulate triglyceride synthesis via prostanoid receptors EP1 and EP3 on hepatocytes (Enomoto et al, 2000). Ethanol also acts on EP2 and EP4 receptors on Kupffer cells to elicit PGE 2 -induced feedback-regulated production of pro-inflammatory cytokines (Fennekohl et al, 2002;Nakatani, et al, 2004). Inhibition of COX-2 leads to suppression of toxicant-induced inflammatory responses in the liver and other organs (Reilly et al, 2001).…”
Section: Introductionmentioning
confidence: 99%